Peripheral Blood Immunological Features Associated with Aortic Valve Disease and Ascending Throcic Aorta Aneurysm and Dilation - Tiwari, Kaushal Kishore; Sbrana, Silverio; Bevilacqua, Stefano; Giungato, Paola; Pucci, Angela; Santaerelli, Filippo; Solinas, Marco; Glauber, Mattia (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Ascending thoracic aortic aneurysm (TAA) is a multi-factorial process in which histological modifications and immune-mediated inflammation are closely associated. The predominant role of a Th1-mediated response in influencing aortic wall remodeling, dilation, and aneurysm formation has been suggested by previous studies. Recently, the importance of chemokine receptors for Th1 cells recruitment into vascular inflammatory sites, as well as of the balance between pro- and anti-inflammatory T-cell subsets in influencing the severity of coronary artery disease, have been described. MATERIAL AND METHODS: We evaluated activation markers and chemokine receptors expression on peripheral T-cell and NK cell subsets of subject with aortic valve disease associated with ascending TAA (ascending aortic diameter > 4 cm) and undergoing elective surgery for TAA (Group A), in comparison with patients with aortic valve disease without TAA (ascending aortic diameter < 4 cm) (Group B). Peripheral blood samples from the two groups were also compared for intracellular T-lymphocyte cytokine production, frequency of regulatory T cells (Treg) and soluble levels of cytokine and chemokines. The aortic size index (ASI) was considered a parameter able to reflect aortic pathophysiological modifications leading to aortic dilation. RESULTS: The results demonstrated correlations between ASI values and CCR5 expression on CD3+, CD3+/CD8+, CD4+ and CD4+/CD28- T-cell subsets. In Group A the expression of CCR5 was higher on CD3+/CD8+, CD4+ and CD4+/CD28- T-cell subsets, when compared with Group B. CD4+ and CD4+/CD28- T-cells in Group A showed also a higher expression for the co-stimulatory molecule CD28 and the activation marker CD25, respectively. An increased expression of CXCR3 was found on CD4+, CD3+/CD8+ and CD3+/TCR+ T-cell subsets in Group A. A higher circulating fraction of NK cells, together with a higher NK cell positivity for CX3CR1, were observed in aneurysmatic patients. Intracellular cytokine analysis demonstrated a higher fraction of CD3+/CD4+ T-cells producing IL-17A and IL-10 in Group A, together with a higher intracellular content for IL-21. Finally, a higher soluble level of fractalkine (CX3CL1) has been detected in aneurysm group. CONCLUSION: Results indicate a higher activation state, migratory capacity and cytotoxic potential of peripheral blood NK and T-cell subsets in patients with aortic valve disease associated with ascending TAA, when compared with patients affected by aortic valve disease alone. These findings, together with the observed higher polarization towards a Th17 in patients with aortic aneurysm could suggest the involvement of autoimmune mechanisms leading to cellular loss, inflammation and fibrosis during ascending aortic wall dilation and aneurysmatic progression. Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 11-20